Article Review: Potential use of Andaliman Fruit as an Antibacterial - Karo-Karo, Sry Ulina; Nabila, Nabila; Hartini, Putri Tri; Andry, Muhammad; Ligo, Azzura; Rezaldi, Firman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This research examines the potential of andaliman fruit (Zanthoxylum acanthopodium) as an antibacterial agent. Andaliman fruit is known to contain bioactive compounds such as alkaloids, flavonoids and saponins which have the potential to inhibit the growth of pathogenic bacteria. The antibacterial activity test was carried out using the agar diffusion method against several test bacteria, including Escherichia coli and Staphylococcus aureus. The results showed that andaliman fruit extract had significant antibacterial activity, indicated by the inhibition zone formed around the extract impregnation disc. The highest activity was noted against Staphylococcus aureus, which is a gram-positive bacterium. These findings indicate that andaliman fruit has the potential to be developed as an effective natural antibacterial agent. Further research is needed to identify the specific active compound and its antibacterial mechanism of action.